2023
DOI: 10.5772/intechopen.107891
|View full text |Cite
|
Sign up to set email alerts
|

Human–Wild Animal Conflict

Abstract: Wildlife species have faced the impacts of human dominion over the world throughout history. More recently, there has been increased global protection for endangered species as a result of greater awareness and concern for biodiversity. Conservationists are becoming increasingly concerned about the pervasive issue of conflicts between human and wildlife interests, especially as it relates to large carnivores that have the potential to harm both cattle and people. Pre-conflict mitigation refers to proactive mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Hence, strategies for conflict mitigation such as the use of deterrents or secure enclosures, raising awareness among local communities, appropriate waste management, responsible food storage, and insurance programs could be suitable solutions (Joshi, 2019;Pathak et al, 2023;Somu & Palanisamy, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, strategies for conflict mitigation such as the use of deterrents or secure enclosures, raising awareness among local communities, appropriate waste management, responsible food storage, and insurance programs could be suitable solutions (Joshi, 2019;Pathak et al, 2023;Somu & Palanisamy, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Himalayan black bears usually hibernate between December to March and in preparation will eat more grains and fruit, venturing farther in search of food (Bashir et al., 2018), potentially leading to more frequent encounters and conflicts with humans. Hence, strategies for conflict mitigation such as the use of deterrents or secure enclosures, raising awareness among local communities, appropriate waste management, responsible food storage, and insurance programs could be suitable solutions (Joshi, 2019; Pathak et al., 2023; Somu & Palanisamy, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In the past two decades, mountain glaciers have been shrinking in and around Sanjiangyuan Nature Reserve of China (SNRC), directly affecting water supplies to plateau lakes and rivers, and further affecting vegetation structure, biodiversity, water conservation and other functions [4][5][6] . Meanwhile, due to this destructive impact of human activities, such as poaching for meat, hides, and fur, excessive livestock grazing, as well as the construction of roads and railways, the original habitat is often lost or fragmented 7 . Many studies have shown that this degradation is a primary factor behind the decline of wild ungulates, attributed mainly to landscape fragmentation and habitat destruction 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Human-wildlife conflicts are often caused by human population increase, high livestock and wildlife population densities, and changing land use and climate (Mukeka, et al 2019). Conservationists are becoming increasingly concerned about the pervasive issue of conflicts between human and wildlife interests, especially as it relates to large carnivores that have the potential to harm both cattle and people (Somu & Selvaraj, 2022). Human-wildlife conflict arises when interferes with human goals, or when human goals interfere with the needs of wildlife over the needs of local people, aggravating the worldwide problem (Meena, et al 2022).…”
Section: Introductionmentioning
confidence: 99%